2020
DOI: 10.1038/s41746-020-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Precision wearable accelerometer contact microphones for longitudinal monitoring of mechano-acoustic cardiopulmonary signals

Abstract: Mechano-acoustic signals emanating from the heart and lungs contain valuable information about the cardiopulmonary system. Unobtrusive wearable sensors capable of monitoring these signals longitudinally can detect early pathological signatures and titrate care accordingly. Here, we present a wearable, hermetically-sealed high-precision vibration sensor that combines the characteristics of an accelerometer and a contact microphone to acquire wideband mechano-acoustic physiological signals, and enable simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…Wearable acoustic sensing technology has emerged for auscultation. Gupta et al have developed a wearable solution that integrates an accelerometer and a microphone via a nano-gap transducer for longitudinal monitoring of heart and lung sounds as well as relevant parameters including HR, RR, and body motion [58]. Klum et al have reported a wearable stethoscope patch that combines sensing modalities like a MEMS stethoscope, ambient noise sensing, ECG, impedance pneumography and 9-axis actigraphy.…”
Section: Lung Soundsmentioning
confidence: 99%
“…Wearable acoustic sensing technology has emerged for auscultation. Gupta et al have developed a wearable solution that integrates an accelerometer and a microphone via a nano-gap transducer for longitudinal monitoring of heart and lung sounds as well as relevant parameters including HR, RR, and body motion [58]. Klum et al have reported a wearable stethoscope patch that combines sensing modalities like a MEMS stethoscope, ambient noise sensing, ECG, impedance pneumography and 9-axis actigraphy.…”
Section: Lung Soundsmentioning
confidence: 99%
“…Numerous innovative and non-invasive tools can be used to detect leg impedance, such as sock-based sensors 51 . Furthermore, microphone-based devices have been used to transform cardiac acoustic vibrations to biomedical signals in quantitative versions of the phonocardiogram 52 . Such devices can track respiratory rate, heart and lung sounds, and body motion or position, and might be superior to physical examination for predicting worsening HF 53 .…”
Section: Innovative Biosensors For Hf Detectionmentioning
confidence: 99%
“…Since the body's center of mass is close to the chest, it is an ideal position for hosting AR systems that aim to classify activities such as walking, running, cycling, jumping and pushing up. AR [32,33], EE estimation [34], fall detection [35] and motion tracking [36] are among the applications addressed using chest-worn IMUs.…”
Section: Activity Analysismentioning
confidence: 99%
“…All the referenced studies (except one [36]) use commercial off-the-shelf IMUs for measurement of the vibrations and movements. They either have their own electronic Printed Circuit Boards (PCBs) equipped with appropriate inertial sensors or incorporate a research-grade off-the-shelf sensor board package such as Shimmer [79].…”
Section: Sensor Specificationsmentioning
confidence: 99%